The role of strategic technology alliances (STA) towards organizational performance in manufacturing industry: the perspective of developing countries - Jabar, Juhaini; Soosay, Claudine; Abdul Khalid, Fararishah; Musa, Haslinda; Othman, Norfaridatul Akmaliah (CCSE, 2015)
This research investigates strategic technology alliances (STA) in Malaysian manufacturing firms and the impact on organizational performance. The outcomes of this paper shed light on the underpinning theories under Resource Based View (RBV) and Organizational Learning (OL) as an antecedent for the successful implementation of strategic technology alliances in the manufacturing industry. At the end of the paper provides a model that describing the success factor of strategic technology alliances en route to improve organizational performance and remain competitive.